(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores the usage of foreign words in English texts and the challenges they present in translation into Uzbek. With globalization and cultural exchange, English has incorporated numerous borrowings from Latin, French, German, and other languages. Translating these terms into Uzbek requires not only linguistic competence but also cultural awareness and contextual understanding. The study analyzes common strategies used in translating foreign words, such as transliteration, calque, descriptive translation, and adaptation. It also highlights frequent issues faced by translators, including untranslatable concepts, preservation of stylistic nuances, and the risk of misinterpretation. The paper provides examples from literary, scientific, and journalistic texts to illustrate effective translation practices.